Efficient degradation of tetracycline under the conditions of high-salt and coexisting substances by magnetic CuFe2O4/g-C3N4 photo-Fenton process. (December 2022) - Sun, Xiyu; Huang, Likun; Wang, Guangzhi; Feng, Huanzhang; Zhou, Simin; Zhao, Rui; Wang, Dongdong; Li, Zhe
Abstract: For the effective degradation of tetracycline (TC), a facilely prepared magnetic CuFe2 O4 /g-C3 N4 (CFO/g) photocatalyst was successfully constructed. The structure, morphology, composition, optical, and magnetic properties of CFO/g were characterized. CFO/g demonstrated excellent photo-Fenton performance of TC in the presence of high-Cl -, NO3 −, HCO3 −, HPO4 2−, SO4 2− and humic acid. Ten cycles of experiments with the removal rate of TC only decreasing by 2.8% confirmed the stability and high activity of CFO/g. The dissolved concentrations of Fe and Cu ions were 0.013 and 0.009 mg L −1, respectively. Its excellent magnetic properties made CFO/g easier to be recycled than traditional catalysts. ·OH and O2 · - were proposed to be the main active species in the photo-Fenton system. The CFO/g heterojunction enhanced the separation of photogenerated electron-hole pairs and visible light absorption range. Furthermore, the identification of intermediates suggested that TC degradation was classified into two pathways, and the most critical and rapid degradation was achieved within the first 30 min. The TC and its intermediates did not significantly inhibit the growth activity of Escherichia coli . This research provided a promising application of magnetic photocatalysts in wastewater treatment of pharmaceuticals and personal care products. Graphical abstract: Image 1 Highlights: A magnetic photocatalyst was constructed with an excellent visible light response. CuFe2 O4 /g-C3 N4 exhibited efficient tetracycline removal under high-salt conditions. CuFe2 O4 /g-C3 N4 exhibited efficient tetracycline removal in the presence of anions. Excellent magnetic properties of CuFe2 O4 /g-C3 N4 facilitated its recycling. Removal mechanism and intermediates of tetracycline were demonstrated.